Virtual network embedding with discrete particle swarm optimisation. Issue 4 (1st February 2014) - Wang, Li; Qu, Hua; Zhao, Jihong; Guo, Ya
Abstract : Network virtualisation is organised as a fundamental technology for eradicating the ossified architecture of the Internet. Virtual network embedding (VNE) instantiates virtual networks on a substrate network to carry as many services as possible, which is an optimisation problem. VNE with discrete particle swarm optimisation (DPSO) is proposed, which models VNE and abstracts its constraints, modifies PSO into DPSO, adapts the characters of VNE and obtains the optimal solution to map virtual networks onto a substrate network.